DUET: A Phase 2 Study Evaluating the Efficacy and Safety of Sparsentan in Patients with FSGS - Trachtman, Howard; Nelson, Peter; Adler, Sharon; Campbell, Kirk N; Chaudhuri, Abanti; Derebail, Vimal Kumar; Gambaro, Giovanni; Gesualdo, Loreto; Gipson, Debbie S; Hogan, Jonathan; Lieberman, Kenneth; Marder, Brad; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: We evaluated and compared the effects of sparsentan, a dual endothelin type A (ETA) and angiotensin II type 1 receptor antagonist, with those of the angiotensin II type 1 receptor antagonist irbesartan in patients with primary FSGS. METHODS: In this phase 2, randomized, double-blind, active-control Efficacy and Safety of Sparsentan (RE-021), a Dual Endothelin Receptor and Angiotensin Receptor Blocker, in Patients with Focal Segmental Glomerulosclerosis (FSGS): A Randomized, Double-blind, Active-Control, Dose-Escalation Study (DUET), patients aged 8-75 years with biopsy-proven FSGS, eGFR>30 ml/min per 1.73 m2, and urinary protein-to-creatinine ratio (UP/C) ≥1.0 g/g received sparsentan (200, 400, or 800 mg/d) or irbesartan (300 mg/d) for 8 weeks, followed by open-label sparsentan only. End points at week 8 were reduction from baseline in UP/C (primary) and proportion of patients achieving FSGS partial remission end point (FPRE) (UP/C: ≤1.5 g/g and >40% reduction [secondary]). RESULTS: Of 109 patients randomized, 96 received study drugs and had baseline and week 8 UP/C measurements. Sparsentan-treated patients had greater reductions in UP/C than irbesartan-treated patients did when all doses (45% versus 19%; P=0.006) or the 400 and 800 mg doses (47% versus 19%; P=0.01) were pooled for analysis. The FSGS partial remission end point was achieved in 28% of sparsentan-treated and 9% of irbesartan-treated patients (P=0.04). After 8 weeks of treatment, BP was reduced with sparsentan but not irbesartan, and eGFR was stable with both treatments. Overall, the incidence of adverse events was similar between groups. Hypotension and edema were more common among sparsentan-treated patients but did not result in study withdrawals. CONCLUSIONS: Patients with FSGS achieved significantly greater reductions in proteinuria after 8 weeks of sparsentan versus irbesartan. Sparsentan was safe and well tolerated.
Keywords: blokátory receptorů AT1 pro angiotensin II; Proteinuria; dospělí; vztah mezi dávkou a účinkem léčiva; Female; dítě; Adult; Glomerulosclerosis, Focal Segmental; mladý dospělý; ženské pohlaví; irbesartan; Adolescent; lidé; dvojitá slepá metoda; Dose-Response Relationship, Drug; Irbesartan; Double-Blind Method; Male; Aged; Young Adult; Creatinine; lidé středního věku; Child; senioři; kreatinin; mužské pohlaví; Angiotensin II Type 1 Receptor Blockers; antagonisté endotelinového receptoru A; Endothelin A Receptor Antagonists; fokálně segmentální glomeruloskleróza; Middle Aged; mladiství; proteinurie; Humans